2017
DOI: 10.1111/bph.14043
|View full text |Cite
|
Sign up to set email alerts
|

A new negative allosteric modulator, AP14145, for the study of small conductance calcium‐activated potassium (KCa2) channels

Abstract: AP14145 is a negative allosteric modulator of K 2.2 and K 2.3 channels that shifted the calcium dependence of channel activation, an effect strongly dependent on two identified amino acids. AP14145 prolonged AERP in rats and did not trigger any acute CNS effects in mice. The understanding of how K 2 channels are inhibited, at the molecular level, will help further development of drugs targeting K 2 channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Within the calcium-activated potassium channels, it was found that the IK channel was not affected by BBP 1 μM (Figures 3A,B) whereas BK channel was inhibited by 19 ± 6% (Figure 4C), an inhibitory effect 4.8-fold lower than on any SK currents. Interestingly, this relation between BK and SK channels has also been observed for the allosteric modulator AP14145 (Simó-Vicens et al, 2017a). In the case of voltage-activated potassium channels, none of the six tested currents (K ir 2.1, K ir 3.1+K ir 3.4, K v 1.5, K v 4.3/K CHIP 2, K v 7.1/KCNE1, hERG) were significantly affected by BBP 10 μM, except for hERG, which was reduced by 19 ± 3% (Figure 6).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Within the calcium-activated potassium channels, it was found that the IK channel was not affected by BBP 1 μM (Figures 3A,B) whereas BK channel was inhibited by 19 ± 6% (Figure 4C), an inhibitory effect 4.8-fold lower than on any SK currents. Interestingly, this relation between BK and SK channels has also been observed for the allosteric modulator AP14145 (Simó-Vicens et al, 2017a). In the case of voltage-activated potassium channels, none of the six tested currents (K ir 2.1, K ir 3.1+K ir 3.4, K v 1.5, K v 4.3/K CHIP 2, K v 7.1/KCNE1, hERG) were significantly affected by BBP 10 μM, except for hERG, which was reduced by 19 ± 3% (Figure 6).…”
Section: Discussionsupporting
confidence: 58%
“…In addition, compounds may not be pharmacologically well characterized and with sufficient SK channel potency or general selectivity. Moreover, expansion of SK channels research, has further challenged currently available pharmacological tools which have been confronted with insensitive heteromeric channels (Hancock et al, 2015), difficult to access intracellular locations (Krabbendam et al, 2018), unexpected inhibitory effects (Voos et al, 2017), and intracellular calcium dependence (Strøbæk et al, 2006; Simó-Vicens et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, apamin cannot be used clinically due to its neurotoxicity. AP14145, a newly synthesized I KAS negative modulator (37), might be a promising candidate for future use in JWS. Amiodarone suppresses I KAS at its therapeutic concentration (10-20 μmol/l) (38).…”
Section: Discussionmentioning
confidence: 99%
“…The small molecule AP30663 selectively inhibits K Ca 2 channels thereby diminishing the current mediated by them, I KCa (Bentzen et al, 2020). Other small-molecule K Ca 2 channel inhibitors give rise to adverse central nervous effects such as vomiting and tremors (Diness et al, 2017;Simó-Vicens et al, 2017), but this does not seem to be the case with AP30663.…”
Section: Introductionmentioning
confidence: 99%